2021
DOI: 10.3390/ani11041109
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Pathogenic Leptospira Species Isolated from Wild Mammal Reservoirs in Sardinia

Abstract: Leptospirosis is a global zoonosis caused by pathogenic species of Leptospira that infect a large spectrum of domestic and wild animals. This study is the first molecular identification, characterization, and phylogeny of Leptospira strains with veterinary and zoonotic impact in Sardinian wild hosts. All samples collected were cultured and analyzed by multiplex real time polymerase chain reaction (qPCR). Sequencing, phylogenetic analyses (based on rrs and secY sequences), and Multilocus Sequence Typing (MLST) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 45 publications
4
13
0
Order By: Relevance
“…Results obtained from the seven isolates from rat kidneys with MLST allowed for the characterization of the Leptospira strains by sequencing and analyzing specific fragments of some bacterial housekeeping genes, thus identifying specific sequence types (STs). These results were in agreement with the recent detection of pathogenic Leptospira from wild mammals [24] in the same study area and indicate that serovar diversity of Leptospira species has yet to be fully investigated in Sardinia Island.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results obtained from the seven isolates from rat kidneys with MLST allowed for the characterization of the Leptospira strains by sequencing and analyzing specific fragments of some bacterial housekeeping genes, thus identifying specific sequence types (STs). These results were in agreement with the recent detection of pathogenic Leptospira from wild mammals [24] in the same study area and indicate that serovar diversity of Leptospira species has yet to be fully investigated in Sardinia Island.…”
Section: Discussionsupporting
confidence: 92%
“…5-Fluorouracil (5-FU) was added due to minimize bacterial contamination. Samples of kidney and liver were homogenized as previously described [24]. A total of 500 µL of urine (500 µL diluted 1:100 in PBS) and 25 mg of tissue were suspended in EMJH-fluorouracil medium at 28 • C and cultured for a period of three months.…”
Section: Culturing Of Leptospiresmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe a host specificity of serogroups and STs for bank voles in our study, as the STs detected in our study were also found in other small mammal species: ST24 was found in the yellow-necked field mouse, the wood mouse, and the Eurasian beaver ( Castor fiber ); ST110 in the yellow-necked field mouse, common vole, field vole and the common shrew ( Sorex araneus ); and ST197 in the common shrew and crowned shrew ( S. coronatus ) [ 53 , 58 , 71 ]. Studies from Europe and Asia also show a high ST diversity among different genera of small mammals [ 72 , 73 , 74 , 75 ]. Serogroups detected in our study were detected worldwide in different host species, e.g., serogroup Australis in swine, goats, cats and dogs [ 76 , 77 , 78 , 79 ]; serogroup Grippotyphosa in cattle, sheep, wild boars, dogs and horses [ 16 , 80 , 81 , 82 , 83 ]; and serogroup Sejroe in cattle [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cases of leptospirosis are registered in all parts of the world inhabited by humans (Vinetz, 2001;Xiao-Juan Ma et al, 2020;Piredda et al, 2021;Philip et al, 2020;Mahtab et al, 2019;Alinaitwe et al, 2019), except Antarctica. Pathogenic leptospira can parasitize in organisms of many species of domestic and wild animals of various systematic and ecological groups.…”
Section: Introductionmentioning
confidence: 99%